Alloparental care of ducklings by unrelated male Speckled Teal Anas flavirostris in eastern Argentina - Port, Jeffrey L (Wildfowl, 2000)
Observations of alloparental behaviour by male Speckled Teal (Anas flavirostris) toward unrelated ducklings in a eucalyptus grove near Santa Teresita, Argentina. Males assisting their mates in nest prospecting were observed defending, and ultimately escorting away from the nest site, unrelated ducklings abandoned at the nest site by the brood female. This is the first recorded observation of alloparental care in this species and provides additional support for the existence of male parental care in this species.